Museum Frictions : Public Cultures/Global Transformations - Rassool, Ciraj; Kirshenblatt-Gimblett, Barbara; Buntinx, Gustavo; Ybarra-Frausto, Tomás, 1938-; Szwaja, Lynn; Kratz, Corinne Ann, 1953-; Karp, Ivan (Book collections on Project MUSE., 2006)
Museum Frictions is the third volume in a bestselling series on culture, society, and museums. The first two volumes in the series, Exhibiting Cultures and Museums and Communities, have become defining books for those interested in the politics of museum display and heritage sites. Another classic in the making, Museum Frictions is a lavishly illustrated examination of the significant and varied effects of the increasingly globalized world on contemporary museum, heritage, and exhibition practice. The contributors--scholars, artists, and curators--present case studies drawn from Africa, Australia, North and South America, Europe, and Asia. Together they offer a multifaceted analysis of the complex roles that national and community museums, museums of art and history, monuments, heritage sites, and theme parks play in creating public cultures. Whether contrasting the transformation of Africa's oldest museum, the South Africa Museum, with one of its newest, the Lwandle Migrant Labor Museum; offering an interpretation of the audio guide at the Guggenheim Bilbao; reflecting on the relative paucity of art museums in Peru and Cambodia; considering representations of slavery in the United States and Ghana; or meditating on the ramifications of an exhibition of Australian aboriginal art at the Asia Society in New York City, the contributors highlight the frictions, contradictions, and collaborations emerging in museums and heritage sites around the world. The volume opens with an extensive introductory essay by Ivan Karp and Corinne A. Kratz, leading scholars in museum and heritage studies. Contributors. Tony Bennett, David Bunn, Gustavo Buntinx, Cuauhtémoc Camarena, Andrea Fraser, Martin Hall, Ivan Karp, Barbara Kirshenblatt-Gimblett, Corinne A. Kratz, Christine Mullen Kreamer, Joseph Masco, Teresa Morales, Howard Morphy, Ingrid Muan, Fred Myers, Ciraj Rassool, Vicente Razo, Fath Davis Ruffins, Lynn Szwaja, Krista A. Thompson, Leslie Witz, Tomás Ybarra-Frausto